The Perceptions Of Youth Community On The Use Of Slang Language On The Maintenance Of Mother Tongue In Pematangsiantar - Panjaitan, Ribka; Hutauruk, Bertaria Sohnata; Dhillon, Bobby Pramjit Singh (Lembaga Riset dan Inovasi Almatani, 2026)
This research aims to analyze the the perceptions of youth community found on the use of slang language on the maintenance of mother tongue and the types of slang used by the youth community in Pematangsiantar. This research uses qualitative descriptive research. Data were taken from the transcript of an interview and youth conversation recordings. The analysis focused on the perceptions of youth community based on Joanes et al. (2014) theory : auditory perception, visual perception, kinesthetic-tactile perception, social perception, extra-sensory perception. The results showed that out of 50 expressions of perception, two out of five types of perception were identified. 48 expressions were categorized as social perception, while the remaining 2 were categorized as auditory perception. In addition, the emergence of filler expressions such as eee, umm, and hmm while the interview process indicates additional oral strategies to maintain the flow of conversation, provide time to organize thoughts, mark hesitation, and also serve as a form of habit. Next, this study identified out of 20 expression of slang language, 17 of them were categorized into seven types of slang language based on theory of Allan & Burridge (2006, as cited in Mulyantini et al., 2023) and Hidayat et al. (2020, as cited in Hasanah 2022) including imitative, clipping, blending, borrowing, multiple process, fresh and creative, and flippant, while the remaining 3 were catergorized into uncategorized slang language. In conclusion, this study confirm that slang is not merely a linguistic variation, but also serves as a social tool supporting interaction, self-expression, and the management of informal conversations